2021
DOI: 10.1002/pbc.28910
|View full text |Cite
|
Sign up to set email alerts
|

A bilingual dietary intervention early in treatment is feasible and prevents weight gain in childhood acute lymphoblastic leukemia

Abstract: Background Childhood acute lymphoblastic leukemia (ALL) is the most common pediatric malignancy. The onset of obesity during childhood ALL has been well established and is associated with inferior survival rates and increased treatment‐related toxicities. This pilot study sought to determine if a dietary intervention is feasible and minimizes weight gain during the initial phases of treatment for ALL. Methods Participants were recruited from four institutions, fluent in English or Spanish, between 5 and 21 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Other nutritional interventions in pediatric oncology have reported improvements in specific aspects of diet over time. Among them, in a multicenter pilot study implementing a nutrition intervention program shortly after a pediatric cancer diagnosis, the authors found an increase in the mean intakes of proteins and vegetables and a decrease in added sugar consumption when the final and initial assessments were compared [ 46 ]. Similar to our results, variations in caloric intakes were observed after the induction phase but did not persist over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other nutritional interventions in pediatric oncology have reported improvements in specific aspects of diet over time. Among them, in a multicenter pilot study implementing a nutrition intervention program shortly after a pediatric cancer diagnosis, the authors found an increase in the mean intakes of proteins and vegetables and a decrease in added sugar consumption when the final and initial assessments were compared [ 46 ]. Similar to our results, variations in caloric intakes were observed after the induction phase but did not persist over time.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have emphasized the difficulty of reversing unhealthy eating behaviors acquired during treatment [ 43 ], and several suggested implementing screening and intervention protocols at diagnosis and throughout treatment [ 44 , 45 ]. Despite these recommendations and the potential impact of diet during and after pediatric cancer, few nutrition interventions have been deployed with this population, and only one initiated early after diagnosis has been documented [ 46 ]. We have previously described the feasibility of an early nutrition intervention for children and adolescents undergoing cancer treatment [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the only one published consists of an 8-module Facebook-based educational intervention for adolescents treated for cancer [ 52 ]. Otherwise, all health promotion interventions for adolescents implemented during cancer treatments included children of all ages or young adults [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 To our knowledge, the study by Walters et al is the first nutritional intervention study undertaken during the induction phase of pediatric ALL therapy. 1 This multi-institutional study was conducted in person or via telemedicine in English or Spanish and offered nutritional counseling and educational materials adapted to the diet preferences of the ethnically and socioeconomically diverse population. Participants represented all four categories of body mass index (BMI) at baseline, with approximately 30% being overweight or obese.…”
mentioning
confidence: 99%
“…In this issue, Walters et al report the results of a pilot study examining the feasibility and impact on weight gain of a nutritional intervention that was initiated during induction and continued through the first 6 months of therapy for acute lymphoblastic leukemia (ALL). 1 Although the survival rate of pediatric ALL is greater than 90% in high-income countries, 2 children with ALL still experience disease-related and treatment-related toxicities that negatively affect their quality of life.…”
mentioning
confidence: 99%